Accelerating Curriculum Transformation: Integrating Stakeholder Commitment into Lewin’s Change Management Model in Kindergartens - Tejaningsih, Endah; Mudofir, Mudofir; Rohmadi, Yusup (JURNAL AL-TANZIM, 2026)
This study aims to analyze curriculum change management in kindergartens, including obstacles and solutions. The approach used was a descriptive qualitative one, with principals and school administrators as research subjects and teachers as informants. This study took place from February to June 2025, with data collected through interviews, document analysis, and triangulation. Data were analyzed using the Miles and Huberman interactive model. The results showed that the curriculum change management process in kindergartens followed the stages proposed by Lewin: the opening stage (planning), the change stage (implementation), and the refreezing stage (evaluation). A novelty found was the existence of accelerating factors in curriculum transformation that had not been specifically discussed in Lewin’s theory. These accelerating factors include the competence and commitment of principals and teachers, as well as good collaboration between internal and external stakeholders. The implications of these findings are the importance of improving the competence of principals and teachers in managing curriculum change, as well as the need to build effective communication between all relevant parties to accelerate the change process. This can be used as a reference in developing a more responsive and sustainable curriculum in kindergartens, thereby supporting the improvement of the quality of education from an early age.